1997
DOI: 10.1080/07315724.1997.10718710
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge, attitudes and practices among senior medical students in Taiwan.

Abstract: The knowledge, attitudes and practices of senior medical students in Taiwan suggest the need for education strategies to improve competence in the area of nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
6
0
2
Order By: Relevance
“…The increasing failure of households to ensure the availability of adequate food and access, thus, hinders the practice of recommended nutrition habits for the PLWHA in these households. Other studies have shown low socioeconomic status, level of education, personal beliefs, availability of food, and low nutrition knowledge as contributory factors to poor dietary practices (16, 2023). …”
Section: Discussionmentioning
confidence: 99%
“…The increasing failure of households to ensure the availability of adequate food and access, thus, hinders the practice of recommended nutrition habits for the PLWHA in these households. Other studies have shown low socioeconomic status, level of education, personal beliefs, availability of food, and low nutrition knowledge as contributory factors to poor dietary practices (16, 2023). …”
Section: Discussionmentioning
confidence: 99%
“…These evaluations can be applied for determination of social health status and important factors in this regard providing sufficient health care services. Determination of nutritional knowledge, attitude and practice of patients can be useful in guiding interventional strategies for health care (4, 5). …”
Section: Introductionmentioning
confidence: 99%
“…According to the Brazilian National Policy for Food and Nutrition (PNAN), a healthy diet is defined as: [...] considering that there are other purposes to food than merely supplying for biological needs, since it has unique cultural, behavioral and emotional meanings that cannot be ignored. 20 Studies have shown that medical students may present limited knowledge in the field of nutrition 21,22 . A research study evaluating students' knowledge of general and clinical nutrition showed an average accuracy of 60 and 52 percent in the replies, respectively.…”
Section: The Need For Balancing Several Sources Of Nutrientsmentioning
confidence: 99%